The complete guide to kettlebell training - Allan Collins (Bloomsbury, 2011)
A kettlebell is a weight that looks like a cannonball with a handle. Originating from Russia, kettlebell training is now a global phenomenon with clubs, gyms and individuals investing in equipment and training. Weights range from 4kg to 48kg. They differ from dumbbells and barbells in that the centre of mass is offset from the handle, so the weight constantly pulls against your hand, improving coordination